Iron-based soft magnetic powder and method for producing the same, and article containing the iron-based soft magnetic alloy powder and method for producing the same
By adjusting the crystallinity and composition of iron-based soft magnetic powder, combined with heat treatment and atomization method, the problem of poor magnetic characteristics of the iron-based soft magnetic powder core after injection molding or pressing is solved, and the excellence under load stress is achieved Magnetic characteristics.
Patent Information
- Application Number
- CN201980023114.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-29
- Filing Date
- 2019-03-28
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2039-03-28
AI Technical Summary
During injection molding or press molding, the best magnetic core characteristics may not be shown after the load stress of the iron-based soft magnetic powder, especially the permeability and core loss.
By adjusting the crystallinity, part of the amorphous phase is crystallized and crystallized are precipitated, iron-based soft magnetic powders contained in Si, B, Cu, and Nb are prepared, and the crystallinity is higher than the coercive force to be minimized by heat treatment. In this state, an iron-based soft magnetic powder with excellent static magnetic properties was prepared in combination with atomization method and a pressurized molding process.
Even under load stress, iron-based soft magnetic powder can exhibit good core magnetic properties, including improving magnetic permeability and reducing core loss.
Smart Images

Figure BDA0002706232380000101 
Figure BDA0002706232380000131 
Figure HDA0002706232390000011
Abstract
Description
Technical Field
[0001] The present invention relates to an iron-based soft magnetic powder showing good magnetic properties even under a stress load, a method for producing the same, and an article containing the iron-based soft magnetic alloy powder and a method for producing the same. Background Art
[0002] The powder core of a choke coil or reactor coil is manufactured by adding an insulating binder such as epoxy resin to soft magnetic powder and molding it into a predetermined shape by injection molding or press molding. At this time, the powder core is manufactured in a state where the soft magnetic powder is loaded with stress.
[0003] Conventionally, as soft magnetic powder used for manufacturing dust cores, there has been used, for example, an iron-based nanocrystalline alloy powder as described in Patent Document 1. This iron-based nanocrystalline alloy powder is manufactured by manufacturing an alloy in an amorphous phase as a whole and then subjecting it to nanocrystallization by heat treatment.
[0004] Then, as disclosed in Patent Document 2, for example, the iron-based soft magnetic alloy powder is subjected to heat treatment to precipitate a bcc phase, and this magnetic powder system is adjusted and used so as to minimize the coercive force.
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 1-79342
[0006] Patent Document 2: Japanese Patent Application Publication No. 2010-280956 Summary of the invention
[0007] However, even when the static magnetic properties (coercive force) of the obtained magnetic powder have been optimized, the following problem still exists: when the magnetic powder is loaded with stress and becomes a pressed powder core through a pressed powder core manufacturing process accompanied by pressurization such as injection molding or press molding, the core may not exhibit the optimal magnetic properties (magnetic permeability, core loss).
[0008] Therefore, the object of the present invention is to provide an iron-based soft magnetic powder and a method for manufacturing the same which exhibit optimal core magnetic properties as a pressed powder core even under stress due to injection molding or press molding, and further to provide an article containing an iron-based soft magnetic alloy powder and a method for manufacturing the same.
[0009] The present inventors have found that when an iron-based soft magnetic powder having excellent static magnetic properties and optimized static magnetic properties is subjected to stress by injection molding or press molding accompanied by pressure and becomes a powder magnetic core, it does not necessarily exhibit the best magnetic core magnetic properties. Then, the present inventors conducted intensive studies and found that by adjusting the crystallinity, even in a state where the iron-based soft magnetic powder is subjected to stress by injection molding or press molding accompanied by pressure, it can exhibit the best magnetic core magnetic properties as a powder magnetic core or the like, thereby completing the present invention.
[0010] That is, the present invention is an iron-based soft magnetic powder, which is an iron-based soft magnetic powder obtained by crystallizing a part of the amorphous phase and precipitating microcrystals through heat treatment, and is characterized in that the iron-based soft magnetic powder contains Si, B, Cu, Nb and inevitable impurities, and has a higher crystallinity than the crystallinity when the coercive force is minimum.
[0011] According to one aspect of the present invention, there is provided the above-mentioned iron-based soft magnetic powder, wherein the iron-based soft magnetic powder has the following composition:
[0012] Fe 100-(x+y+z+r) Si x B y Cu z Nb r
[0013] [Wherein, x, y, z, and r are expressed in at%, satisfying
[0014] 3.0≤x≤16.0
[0015] 6.0≤y≤13.0
[0016] 0.5≤z≤2.0
[0017] 0.5≤r≤4.0
[0018] 1.5≤z+r≤4.5
[0019] 11.5≤y+r≤14.5
[0020] relationship].
[0021] According to one aspect of the present invention, there is provided the above-mentioned iron-based soft magnetic powder, wherein the crystallinity is 80 to 95%.
[0022] According to one aspect of the present invention, there is provided the iron-based soft magnetic powder, wherein the powder hardness measured in accordance with ISO14577-1 is 1000 to 1250 HV.
[0023] According to one aspect of the present invention, there is provided the above-mentioned iron-based soft magnetic powder, which is substantially spherical.
[0024] According to one aspect of the present invention, there is provided the iron-based soft magnetic powder, wherein the average particle size is 0.5 to 50 μm.
[0025] According to one aspect of the present invention, there is provided the above-mentioned iron-based soft magnetic powder, wherein 0.5 to 2.0 at % of Fe is substituted with Cr.
[0026] According to one aspect of the present invention, there is provided an article including the iron-based soft magnetic powder subjected to stress by pressure molding.
[0027] According to one aspect of the present invention, there is provided the above-mentioned article which is a powder magnetic core.
[0028] According to one aspect of the present invention, there is provided a method for producing an iron-based soft magnetic powder, the method comprising the following steps:
[0029] ·1st process
[0030] A step of weighing raw materials so that Fe, Si, B, Cu, and Nb constituting the iron-based soft magnetic powder have a predetermined composition and melting them to obtain an alloy melt;
[0031] · Second process
[0032] A step of obtaining substantially spherical amorphous particles from the alloy melt obtained in the first step by an atomization method;
[0033] ·3rd process
[0034] A step of heat-treating the amorphous particles obtained in the second step to crystallize a part of the amorphous phase and precipitate microcrystals, wherein the crystallinity is made higher than the crystallinity at which the coercive force is minimum.
[0035] According to one aspect of the present invention, there is provided a method for producing the above-mentioned iron-based soft magnetic powder, wherein in the first step, raw materials are weighed so as to have the following composition, and the raw materials are melted to obtain an alloy melt,
[0036] Fe 100-(x+y+z+r) Si x B y Cu z Nb r
[0037] [Wherein, x, y, z, and r are expressed in at%, satisfying
[0038] 3.0≤x≤16.0
[0039] 6.0≤y≤13.0
[0040] 0.5≤z≤2.0
[0041] 0.5≤r≤4.0
[0042] 1.5≤z+r≤4.5
[0043] 11.5≤y+r≤14.5
[0044] relationship.]
[0045] According to one aspect of the present invention, there is provided the method for producing the iron-based soft magnetic powder, wherein the heat treatment temperature in the third step is higher than the heat treatment temperature at which the coercive force is minimum and lower than the crystallization temperature of the amorphous phase.
[0046] According to one aspect of the present invention, there is provided the method for producing the iron-based soft magnetic powder, wherein the crystallinity in the third step is set to 80 to 95%.
[0047] According to one aspect of the present invention, there is provided a method for producing the above-mentioned iron-based soft magnetic powder, wherein the hardness of the powder is set to be smaller than the hardness at which the coercive force is minimum.
[0048] According to one aspect of the present invention, there is provided a method for producing the above-mentioned iron-based soft magnetic powder, wherein the powder has a hardness of 1000 to 1250 HV as measured by a powder hardness meter in accordance with ISO14577-1.
[0049] According to one aspect of the present invention, there is provided a method for producing the above-mentioned iron-based soft magnetic powder, wherein the average particle size is 0.5 to 50 μm.
[0050] According to one aspect of the present invention, there is provided a method for producing the above-mentioned iron-based soft magnetic powder, wherein in the method for producing the above-mentioned iron-based soft magnetic powder, 0.5 to 2.0 at % of Fe is replaced by Cr.
[0051] According to one aspect of the present invention, there is provided a method for producing an article, comprising a pressure-forming step after the above-mentioned method for producing an iron-based soft magnetic powder.
[0052] According to one aspect of the present invention, there is provided a method for manufacturing the above-mentioned article, wherein the article is a powder magnetic core.
[0053] Effects of the Invention
[0054] According to the iron-based soft magnetic powder and the method for manufacturing the same of the present invention, in an iron-based soft magnetic powder containing Si, B, Cu, and Nb and obtained by crystallizing a part of the amorphous phase and precipitating microcrystals through heat treatment, by making the crystallinity higher than the crystallinity at which the coercive force is minimum, the powder can exhibit good magnetic properties as a pressed powder core or the like even when the powder is loaded with stress due to injection molding or press molding. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a diagram illustrating the relationship between crystallinity and magnetic permeability in Examples.
[0056] Figure 2 This is a diagram for explaining the relationship between crystallinity and core loss in Examples. DETAILED DESCRIPTION
[0057] Hereinafter, one embodiment of the present invention will be described in detail. The present invention is not limited to the following embodiments, and can be implemented by adding appropriate changes within the scope that does not impair the effect of the present invention. In addition, in the following description, "A to B" means "A or more and B or less".
[0058] The iron-based soft magnetic powder of the present embodiment is an iron-based soft magnetic powder containing Si, B, Cu, and Nb, and is formed by crystallizing a part of the amorphous phase and precipitating microcrystals by heat treatment. In this iron-based soft magnetic powder, an alloy in which microcrystals of a body-centered cubic structure (bcc phase) with Fe as the main component and microcrystals of a face-centered cubic structure (fcc phase) with Cu as the main component are dispersed in the amorphous phase can be formed by heat treatment, and excellent static magnetic properties can be obtained.
[0059] Then, since the precipitation morphology of the nanocrystals can be changed by the heat treatment temperature, the static magnetic properties of the iron-based soft magnetic powder can be adjusted to a desired state.
[0060] In particular, when the iron-based soft magnetic powder has the following composition, it can exhibit better magnetic properties when used in a powder core or the like under stress due to pressure molding such as injection molding or press molding.
[0061] Fe 100-(x+y+z+r) Si x B y Cu z Nb r
[0062] [Wherein, x, y, z, and r are expressed in at%, satisfying
[0063] 3.0≤x≤16.0
[0064] 6.0≤y≤13.0
[0065] 0.5≤z≤2.0
[0066] 0.5≤r≤4.0
[0067] 1.5≤z+r≤4.5
[0068] 11.5≤y+r≤14.5
[0069] relationship.]
[0070] Si improves the ability to form an amorphous phase. In order to have sufficient ability to form an amorphous phase and obtain good magnetic properties, the amount of Si x is preferably set to a substantially constant ratio of Si / Fe to Fe, 3.0 to 16.0 at%.
[0071] B and Nb improve the ability to form an amorphous phase. In particular, when an iron-based soft magnetic powder is produced by an atomization method, Nb is an essential component. Here, when the amount of B is 6.0 at% or more, the ability to form an amorphous phase becomes larger, and when it is 13.0 at% or less, good magnetic properties are exhibited, so it is preferred.
[0072] The sum y+r of the amount of B y and the amount of Nb r is preferably 11.5≤y+r≤14.5 (at%). When it is 11.5 at% or more, the ability to form an amorphous phase becomes greater, and when it is 14.5 at% or less, good magnetic properties are exhibited.
[0073] Cu and Nb are elements with the effect of controlling the particle size of the nanocrystals precipitated. Here, the effect of controlling the nanocrystal particle size is greatly affected by the Cu amount. When the Cu amount z is more than 0.5at%, it is easy to obtain a nanocrystal with a particle size number controlled to be 10nm and dispersed in the amorphous phase. Thus, the iron-based soft magnetic powder showing good magnetic properties after the heat treatment can be made. In addition, when below 2.0at%, it shows good magnetic properties, so it is preferred.
[0074] Furthermore, the sum z+r of the Cu content z and the Nb content r is preferably 1.5≤z+r≤4.5 (at%). When it is 1.5 at% or more, it can effectively control the particle size of nanocrystals, and when it is 4.5 at% or less, it shows good magnetic properties.
[0075] The iron-based soft magnetic powder formed by the heat treatment described below has a higher crystallinity than that when the coercive force is minimum in the powder state.
[0076] The crystallinity of the iron-based soft magnetic powder is preferably 80 to 95%. Thus, an iron-based soft magnetic powder can be produced that exhibits good magnetic properties even when used in magnetic parts manufactured under a compressive stress.
[0077] The "crystallinity" in the present invention is the ratio of the crystalline phase precipitated in the powder. For example, "crystallinity 80%" means that the ratio of the crystalline phase is 80%, and the remaining 20% is an amorphous phase. The "crystallinity" in the present invention is calculated by the following peak separation using the X-ray diffraction method. (Rigaku Co., Ltd. (published in 2010). X-ray Analysis Handbook (6th edition) Rigaku Co., Ltd.)
[0078] (1) Background separation
[0079] A straight line is drawn from the low-angle side to the high-angle side by linear approximation, and the area below the straight line is set as the background.
[0080] (2) Separation of halo
[0081] The halo pattern is estimated to be caused by the amorphous component, and the halo part is separated from the scattering curve obtained after subtracting the background.
[0082] (3) Separation of crystalline diffraction lines
[0083] The crystalline diffraction lines are separated by the same method as in the above (2).
[0084] (4) Calculation of crystallinity
[0085] The crystallinity was calculated by the following formula using the areas under the curves (integrated intensities) of the diffraction curves of the amorphous component and the crystalline component separated from the total scattering curve.
[0086] (Mathematical formula 1)
[0087] Xc=Ic / (Ic+Ia)
[0088] Xc: crystallinity, Ic: crystalline scattering intensity, Ia: amorphous scattering intensity
[0089] The powder core of a choke coil or reactor coil is manufactured by adding an insulating binder such as epoxy resin to soft magnetic powder and molding it into a predetermined shape by injection molding or press molding. At this time, the powder core is manufactured in a state where the soft magnetic powder is loaded with stress.
[0090] The hardness of the iron-based soft magnetic powder is preferably 1000 to 1250 HV. This allows the powder to have good fluidity during injection molding or press molding, and thus can provide an iron-based soft magnetic powder that exhibits good magnetic properties when made into a powder core or the like.
[0091] The iron-based soft magnetic powder is formed into a roughly spherical shape. As a result, the filling rate of the iron-based soft magnetic powder in the powder core can be increased during injection molding or compression molding, thereby improving the magnetic properties. Here, not all powder shapes need to be roughly spherical. For example, when the major diameter of the particle is a and the minor diameter is b, the particles that satisfy the relationship of 1≤a / b≤1.2 can be more than 70%.
[0092] If the average particle size of the iron-based soft magnetic powder is 0.5 to 50 μm, the filling rate of the iron-based soft magnetic powder can be increased while ensuring the insulation of the powder core when it is made into a powder core, so the magnetic properties can be improved. If the particle size is small, the eddy current loss becomes small when the powder core is used in a high frequency band, so it can be low-loss, but when the particle size is too small, it is impossible to obtain sufficient magnetic permeability μ, so it is preferably 0.5 μm or more. In addition, if the average particle size of the iron-based soft magnetic powder is less than 10 μm, when the powder core is used in a high frequency band above 1 MHz, the eddy current loss can be reduced, and the necessary and sufficient magnetic permeability μ can be obtained, so it is more preferred.
[0093] The article of this embodiment includes the above-mentioned iron-based soft magnetic powder loaded with stress due to pressure molding. The article of this embodiment is a soft magnetic component used for various purposes such as electronic devices or automobile components, etc., especially a pressed powder magnetic core. The article containing the above-mentioned iron-based soft magnetic powder loaded with stress due to pressure molding such as injection molding or compression molding, especially a pressed powder magnetic core, exhibits good core magnetic properties (magnetic permeability, core loss) due to the characteristics of the above-mentioned iron-based soft magnetic powder.
[0094] (Manufacturing method)
[0095] A method for producing the above-mentioned iron-based soft magnetic powder will be described.
[0096] In the first step, raw materials are weighed so that Fe, Si, B, Cu, and Nb have a predetermined composition (for example, the preferred composition shown below), and the raw materials are melted to obtain an alloy melt.
[0097] Fe 100-(x+y+z+r) Si x B y Cu z Nb r
[0098] [Wherein, x, y, z, and r are expressed in at%, satisfying
[0099] 3.0≤x≤16.0
[0100] 6.0≤y≤13.0
[0101] 0.5≤z≤2.0
[0102] 0.5≤r≤4.0
[0103] 1.5≤z+r≤4.5
[0104] 11.5≤y+r≤14.5
[0105] relationship.]
[0106] In the subsequent second step, substantially spherical amorphous particles are obtained from the alloy melt obtained in the first step by an atomization method.
[0107] In this embodiment, a known water atomization method is used. The alloy melt obtained in the first step is dropped from the melt orifice, and the molten raw material is rapidly solidified by the water film sprayed from the atomizing nozzle. The powder is recovered, and after drying and classification, amorphous particles with a predetermined particle size having a roughly spherical particle shape can be obtained.
[0108] In the subsequent third step, the amorphous particles obtained in the second step are heat treated to crystallize a part of the amorphous phase. At this time, the crystallinity of the powder is made higher than the crystallinity when the coercive force is the minimum.
[0109] The heat treatment system in the present invention is used to isothermally maintain a predetermined temperature in a nitrogen atmosphere to crystallize a portion of the amorphous phase and precipitate nanocrystals of tens of nanometers to adjust the magnetic properties. Here, the heat treatment can also be performed in the atmosphere without considering preventing oxidation of the powder.
[0110] When the thermal analysis (DSC) curve of the iron-based soft magnetic powder is taken, two exothermic peaks can be seen. The temperature Tx of the exothermic peak on the low temperature side is the bcc phase precipitation temperature of the body-centered cubic structure crystal phase, and the temperature T1 of the exothermic peak on the high temperature side is the amorphous phase crystallization temperature.
[0111] In the iron-based soft magnetic powder of the present invention, an alloy in which microcrystals of a body-centered cubic structure (bcc phase) with Fe as the main component and microcrystals of a face-centered cubic structure (fcc phase) with Cu as the main component are dispersed in an amorphous phase can be formed by heat treatment, thereby obtaining excellent static magnetic properties.
[0112] Then, since the precipitation morphology of the nanocrystals can be changed by the heat treatment temperature, the static magnetic properties of the iron-based soft magnetic powder can be adjusted to a desired state.
[0113] Important magnetic properties that reflect the properties of the powder core are the magnetic permeability μ and the core loss Pcv. Here, the higher the magnetic permeability μ, the lower the core loss Pcv.
[0114] In the powder state, when the coercive force Hc is low, the magnetic permeability μ becomes high and the core loss can be reduced. Therefore, conventionally, heat treatment is performed so that the coercive force Hc is minimized.
[0115] However, even when the static magnetic properties (coercive force) of the obtained magnetic powder have been optimized, the following problem still exists: when the magnetic powder is loaded with stress and becomes a pressed powder core through a pressed powder core manufacturing process such as injection molding or press molding, the core may not exhibit the optimal magnetic properties (magnetic permeability, core loss).
[0116] When the heat treatment temperature exceeds the heat treatment temperature T2 at which the coercive force Hc is the smallest, the coercive force Hc increases, which is not a preferred condition from the perspective of the static magnetic properties of the powder. At this time, the crystallinity increases and the hardness decreases.
[0117] On the other hand, at heat treatment temperatures higher than heat treatment temperature T2 at which the coercive force Hc is minimum, there is a heat treatment temperature T3 at which the magnetic permeability μ representing the core magnetic characteristics of the dust core reaches a maximum value and the core loss reaches a minimum value.
[0118] The inventors have discovered an iron-based soft magnetic powder that exhibits optimal core magnetic properties (magnetic permeability, core loss) by setting the heat treatment temperature to T3, which is higher than the heat treatment temperature T2 at which the coercive force Hc is minimum and lower than the crystallization temperature T1 of the amorphous phase, and adjusting the crystallinity, hardness, etc.
[0119] The heat treatment temperature T3 is preferably set so that the crystallinity of the iron-based soft magnetic powder becomes 80 to 95%.
[0120] Furthermore, it is preferable to set the heat treatment temperature T3 so as to reach 1000 to 1250 HV.
[0121] Thereby, when stress is applied to the powder magnetic core by injection molding or press molding in the powder magnetic core manufacturing process to form the powder magnetic core, an iron-based soft magnetic powder having optimal core magnetic characteristics can be obtained.
[0122] The manufacturing method of the article of this embodiment includes a pressurization step after the manufacturing method of the above-mentioned iron-based soft magnetic powder. The article (especially the pressed powder core) obtained by the manufacturing method of the pressed powder core of this embodiment shows good core magnetic properties (magnetic permeability, core loss) due to the characteristics of the above-mentioned iron-based soft magnetic powder.
[0123] (Change Example)
[0124] When using powder cores in electronic parts, materials with high corrosion resistance to moisture, etc. are required. In the iron-based soft magnetic powder, 0.5 to 2.0 at% of Fe may be replaced with Cr. This can improve corrosion resistance while maintaining good magnetic properties.
[0125] As the atomization method, a gas atomization method, an oil atomization method, or the like may be adopted.
[0126] According to the iron-based soft magnetic powder and its manufacturing method of the present invention, by making the crystallinity higher than the crystallinity at which the coercive force is minimum, it is possible to produce an iron-based soft magnetic powder which exhibits good core magnetic properties even when the iron-based soft magnetic powder is loaded with stress due to injection molding or press molding.
[0127] Example
[0128] The following are examples of the present invention, but the contents of the present invention are not limited to these examples.
[0129] The mixed materials of the compositions shown in Table 1 were melted in a high-frequency induction furnace and soft magnetic powders were obtained by water atomization. The table also shows the results of the bcc phase precipitation temperature Tx and the saturation magnetization (Bs). The evaluation powder production conditions are shown below.
[0130] <Water atomization conditions>
[0131] Water pressure: 100MPa
[0132] Water volume: 100L / min
[0133] Water temperature: 20℃
[0134] Orifice diameter:
[0135] · Melt raw material temperature: 1800℃
[0136] [Table 1]
[0137]
[0138] Then, the obtained soft magnetic powder is recovered and dried by a vibration vacuum dryer (VU-60: manufactured by Chuo Kako Kikai Co., Ltd.). Since the drying is carried out in a reduced pressure atmosphere, it is possible to dry in a low oxygen atmosphere compared to the drying method carried out in an atmospheric pressure atmosphere, and it is also possible to dry in a short time at a low temperature. Furthermore, by applying vibration to the soft magnetic powder during drying, it is possible to dry in a shorter time, and the powder can be prevented from agglomerating or oxidizing. In this embodiment, the drying temperature is 100°C, the pressure in the drying chamber is -0.1MPa (gauge pressure), and the drying time is 60 minutes.
[0139] Next, the obtained soft magnetic powder was classified by an airflow classifier (Turbo Classifier: manufactured by Nissin Engineering Co., Ltd.) to obtain a powder material having a target average particle size (6 μm, 2 μm). The particle size distribution of the powder material was measured by a laser diffraction particle size distribution measuring device (MT3300EXII: manufactured by Microtrac Bel Co., Ltd.).
[0140] Then, the crystallite size, crystallinity, hardness and coercive force Hc of the obtained soft magnetic powder were evaluated.
[0141] The measuring apparatus and measuring conditions of the crystallite diameter and crystallinity are as follows.
[0142] ·Measurement device: Powder X-ray diffraction device (MinFlex600: manufactured by Rigaku Corporation)
[0143] ·Measurement conditions: voltage 40kV, current 15mA, step width 0.01 degree, speed 1 degree / minute
[0144] The crystallite diameter was calculated for the bcc FeSi peak using the Scherrer formula shown below: Here, the peak near 78° was used as the FeSi peak.
[0145] [Mathematical formula 2]
[0146] Crystallite size
[0147] κ: Scherrer constant
[0148] λ: wavelength of the X-ray lamp
[0149] β: The broadening of the diffraction lines caused by the size of the crystallite
[0150] θ: diffraction angle 2θ / θ
[0151] The hardness measuring device and the measuring method are as follows.
[0152] ·Measurement device: Nanoindenter (ENT-2000: manufactured by ELIONIX Corporation)
[0153] Measurement method: According to ISO14577-1, a load of 5 μN to 100 mN is applied to the cross section of the particle, and the size of the indentation is measured to calculate the powder hardness.
[0154] The measuring device and method of the coercive force Hc are as follows.
[0155] ·Measurement device: Vibrating sample type magnetometer (VSM-C7: manufactured by Toei Industry Co., Ltd.)
[0156] Measurement method: 200 mg of the obtained powder material having each particle size distribution was filled into a capsule for VSM measurement, fixed with paraffin, and a maximum magnetic field of 10,000 Oe was applied to measure the saturation magnetization (Bs) and coercive force (Hc).
[0157] Then, the obtained powder materials having various particle size distributions were mixed with epoxy resin (binder) and toluene (organic solvent) to obtain a mixture. The amount of epoxy resin added was 3% by weight relative to the soft magnetic powder material.
[0158] The thus prepared mixture was heated at 80° C. for 30 minutes and dried to obtain a block-shaped dry product. The dry product was then passed through a sieve with a mesh size of 200 μm to prepare a powder material (granulated product).
[0159] This powder material was filled in a molding die, and a compact (powder magnetic core) was obtained under the following conditions.
[0160] <Molding conditions>
[0161] Molding method: pressing
[0162] Shape of the molded body: Ring
[0163] Molding size: outer diameter 13mm, inner diameter 8mm, thickness 2mm
[0164] Molding pressure: 5t / cm 2 (490MPa)
[0165] · Molding hardening conditions: 150°C, 30 minutes
[0166] <Coil Manufacturing Conditions>
[0167] A conducting wire was wound around the molded body under the following conditions to produce a choke coil.
[0168] Wire material: Cu
[0169] Wire diameter: 0.2mm
[0170] Number of windings: 45 turns for the first winding and 45 turns for the second winding
[0171] <Measurement Conditions and Evaluation>
[0172] The core magnetic properties (μ, Pcv) of the choke coil manufactured under the above conditions were evaluated under the following conditions.
[0173] ·Measurement device: AC magnetic characteristics measurement device (BH analyzer SY8258 manufactured by Yantong Measurement)
[0174] ·Measurement frequency: 1MHz
[0175] Magnetic permeability μ measurement conditions: applied magnetic field 10mT
[0176] Core loss measurement conditions: applied magnetic field 25mT
[0177] The evaluation results are shown below. For compositions 7 and 8, the heat treatment conditions were set to the following 6 levels, and for compositions with different crystallinity, the coercivity Hc and hardness HV in the powder state, and the magnetic properties of the powder core (magnetic permeability μ, core loss) were evaluated. The evaluation results are shown in Table 2. Figure 1 , 2 Here, in Table 2, Test 1 corresponds to the result of Composition 7, and Test 2 corresponds to the result of Composition 8.
[0178] [Table 2]
[0179]
[0180] In both Tests 1 and 2, the crystallinity increases with the increase of the heat treatment temperature, and the amorphous phase is completely crystallized at 600° C. Here, it can be considered that the crystallization temperature of the amorphous phase is about 600° C. In addition, it is estimated that the reason for starting crystallization from 500° C. below the bcc phase precipitation temperature Tx is that there is a portion where the local temperature is higher than the set temperature due to the exothermic reaction of the powder, etc.
[0181] In addition, as for the static magnetic properties of the powder, the coercive force Hc was low and the best magnetic properties were shown when the heat treatment was performed at 530°C (Test 1-3, Test 2-3). At this time, the crystallinity was 76 in Test 1-3 and 74 in Test 2-3. In addition, the hardness HV was 1250 HV in Test 1-3 and 1270 HV in Test 2-3, showing the highest values respectively.
[0182] Conventionally, this state was set as the target state, and the heat treatment temperature was set to 530°C.
[0183] When the heat treatment temperature exceeds 530° C., the heat treatment temperature at which the coercive force Hc is minimum, the coercive force Hc increases, which is not a preferable condition in terms of the static magnetic properties of the powder.
[0184] Here, when the heat treatment temperature exceeds 530° C., the crystallinity increases. In addition, the particle size of the precipitated crystallites increases, and the hardness HV decreases.
[0185] On the other hand, among the core magnetic properties of the dust core, at a heat treatment temperature of 570° C., the magnetic permeability μ exhibited a maximum value, and the core loss exhibited a minimum value.
[0186] like Figure 1 As shown, the crystallinity having the same magnetic permeability as the magnetic permeability of the crystallinity when the coercive force Hc is minimum (heat treatment temperature 530° C.) is 94% in Test 1 and 93% in Test 2.
[0187] like Figure 2 As shown, the crystallinity that exhibits the same core loss as the core loss of the crystallinity when the coercive force Hc is minimum is 91% in both Test 1 and Test 2.
[0188] That is, it can be confirmed that the conditions for the best magnetic properties of the powder core are that the heat treatment temperature is higher than the heat treatment temperature at which the coercive force is the minimum and lower than the crystallization temperature of the amorphous phase, and the crystallinity is higher than the crystallinity at which the coercive force Hc is the minimum. In addition, it can be confirmed that when the heat treatment is performed at an excessive temperature, the crystallinity becomes too high and the magnetic properties of the core deteriorate. From this, it can also be confirmed that the crystallinity is preferably set to 80 to 95%.
[0189] In addition, the same tendency was confirmed in Compositions 1 to 6.
[0190] From the above, it can be confirmed that the iron-based soft magnetic powder becomes a material having the best magnetic properties of the magnetic core when it is made into a powder magnetic core under the composition, crystallinity and hardness specified in the present invention.
Claims
1. An iron-based soft magnetic powder, which is an iron-based soft magnetic powder obtained by crystallizing a part of an amorphous phase and precipitating microcrystals by heat treatment, characterized in that: Contains Si, B, Cu, Nb and unavoidable impurities. The crystallinity is higher than the crystallinity at which the coercivity is the minimum. The iron-based soft magnetic powder has the following composition: Fe 100-(x+y+z+r) And x B y With z Nb r Where x, y, z, and r are expressed in at%, satisfying 3.0≤x≤16.0 6.0≤y≤13.0 0.5≤z≤2.0 0.5≤r≤4.0 1.5≤z+r≤4.5 11.5≤y+r≤14.5 relationship, The crystallinity is 80-95%.
2. The iron-based soft magnetic powder according to claim 1, characterized in that The powder hardness measured according to ISO14577-1 is 1000-1250 HV.
3. The iron-based soft magnetic powder according to claim 1 or claim 2, characterized in that: When the major axis of a particle is a and the minor axis is b, 70% or more of the particles satisfy the relationship of 1≤a / b≤1.
2.
4. The iron-based soft magnetic powder according to claim 1 or claim 2, characterized in that: The average particle size is 0.5 to 50 μm.
5. The iron-based soft magnetic powder according to claim 1 or claim 2, characterized in that: 0.5 to 2.0 at% of Fe is replaced by Cr.
6. An article comprising the iron-based soft magnetic powder according to claim 1 or claim 2 loaded with stress by pressure molding.
7. The article according to claim 6, which is a powder magnetic core.
8. A method for producing an iron-based soft magnetic powder, characterized in that: The process includes the following steps: ·1st process The process of weighing raw materials so that Fe, Si, B, Cu, and Nb constituting the iron-based soft magnetic powder have the following composition and melting them to obtain an alloy melt: Fe 100-(x+y+z+r) And x B y With z Nb r Where x, y, z, and r are expressed in at%, satisfying 3.0≤x≤16.0 6.0≤y≤13.0 0.5≤z≤2.0 0.5≤r≤4.0 1.5≤z+r≤4.5 11.5≤y+r≤14.5 relationship; · Second process A step of obtaining amorphous particles in which 70% or more of the particles satisfy the relationship of 1≤a / b≤1.2 when the major diameter of the particles is a and the minor diameter is b, from the alloy melt obtained in the first step by an atomization method; ·3rd process A step of heat-treating the amorphous particles obtained in the second step to crystallize a part of the amorphous phase and precipitate microcrystals, wherein the crystallinity is higher than the crystallinity at which the coercive force is minimum, The crystallinity in this step is set to 80 to 95%.
9. The method for producing an iron-based soft magnetic powder according to claim 8, characterized in that: The heat treatment temperature in the third step is higher than the heat treatment temperature at which the coercive force is minimum and lower than the crystallization temperature of the amorphous phase.
10. The method for producing the iron-based soft magnetic powder according to claim 8 or claim 9, characterized in that: Make the powder hardness smaller than the hardness when the coercive force is the minimum.
11. The method for producing an iron-based soft magnetic powder according to claim 8, characterized in that: The powder hardness is set to 1000 to 1250 HV using a powder hardness meter measured in accordance with ISO 14577-1.
12. The method for producing the iron-based soft magnetic powder according to claim 8 or claim 9, characterized in that: The average particle size is set to 0.5 to 50 μm.
13. The method for producing an iron-based soft magnetic powder according to claim 8 or claim 9, characterized in that: 0.5 to 2.0 at% of Fe is replaced by Cr.
14. A method for producing an article, comprising a pressure-molding step after the method for producing the iron-based soft magnetic powder according to claim 8 or claim 9.
15. The method for manufacturing an article according to claim 14, wherein the article is a powder magnetic core.
Citation Information
Patent Citations
Fe-base soft magnetic alloy and its production
JP1989079342A
METHOD FOR PRODUCING Fe-BASED SOFT MAGNETIC ALLOY POWDER
JP2010280956A
Method of manufacturing soft magnetic dust core and soft magnetic dust core
CN107851507A
Heat treatment of amorphous core
JP1984040502A